Erdöl, Mais und Devisen. Die ostdeutsch-sowjetischen Wirtschaftsbeziehungen 1951-1967. Eine Dokumentation - Malycha, Andreas (Schriftenreihe der Vierteljahrshefte für Zeitgeschichte, 2016)
The vacillating and tense history of East German&#8211Soviet economic relations in the 1950s and 60s is revealed for the first time through key documents from Moscow archives.